FORMULASI GRANUL INSTAN EKSTRAK BUAH BUNI (Antidesma bunius L.) SEBAGAI MINUMAN ANTIOKSIDAN - Suryani Tawali; Jalil Genisa, Nur Khairi; Amriani Sapra; Maulita Indrisari (BPFP Faperta UNIB, 2024)
Buni is a plant that is widespread in Asia, especially Indonesia. Buni fruit has been reported to contain anthocyanins which have activity as flavonoids, antiocyanins, saponins, alkaloids and as high antioxidant agents, but because Buni fruit is seasonal so raw materials depend on the season, therefore to increase availability it needs to be extracted and formulated in a form preparations. The purpose of this study was to obtain an instant granule formula that meets the physical characteristics and to determine the IC50 value of the antioxidant activity of the instant granule preparation of buni fruit extract (Antidesma bunius L.). The extract was prepared by extraction method using 70% ethanol solvent with the addition of 3% citric acid for 3x24 hours. Instant granules were prepared using the wet granulation method using varying concentrations of PVP as a binder, namely 1%, 3% and 5%. Furthermore, the physical characteristics were evaluated including flow properties, moisture content, soluble time, then antioxidant activity was determined based on the IC50 value using the DPPH method. The results showed that F1 and F2 had good flow properties and F3 had very good flow properties, the moisture content was around 2-4% and the dissolution time was 2-3 minutes. Based on the test results obtained formula 3 with a PVP concentration of 5% is a formula that meets the physical requirements of granules and an IC50 value of 65.94 µg/mL is included in the strong antioxidant category.